Optimal prescription for superior outcomes: a comparative analysis of inter-individual variability in adaptations to small-sided games and short sprint interval training in young basketball players - Xu, H.; Song, J.; Li, G.; Wang, H. (Journal of Sports Science & Medicine, 2024)
Key Points